USE OF HOMEO DRUG FOR CURING ULCERATIVE SYNDROME IN FISHES - MITRA, S. D.; VARSHNEY, P. K. (Journal of Indian Fisheries Association, 2015)
Fungal infection was observed in Catla catla and Labeo rohita cultured in two private fJSh farm5 initially. In later stage it resulted in ulceration followed by haemorrhage on the dorsal surface of the body. Initially, usual treatments of copper sulphate, potassium permanganate and common salt solution were tried, but no improvement was observed. Then repeated intramuscular injections of homeopathic drug Heaper Sulpher and Arnica spray were given wilh encouraging results. Infection reported in another farm was also successfully controlled using a similar treatment